Multimodal assessment of sensorimotor shoulder function in patients with untreated anterior shoulder instability and asymptomatic handball players - Mornieux, G.; Hirschmüller, A.; Gollhofer, A.; Südkamp, N. P.; Maier, D. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: Functional evaluation of sensorimotor function of the shoulder joint is important for guidance of sports-specific training, prevention and rehabilitation of shoulder instability. Such assessment should be multimodal and comprise all qualities of sensorimotor shoulder function. This study evaluates feasibility of such multimodal assessment of glenohumeral sensorimotor function in patients with shoulder instability and handball players.